Adoption of ratio factors for extending part lactation milk records for Red Chittagong Cattle in Bangladesh - Md. Ruhul Amin; Md. Ahsan Habib; A.K. Fazlul Haque Bhuiyan (2012)
Ratio factors for extending part lactation milk yield to a mature equivalent (ME), twice a day (2X) milking and 305-day basis were constructed for Red Chittagong Cattle (RCC) reared at Bangladesh Agricultural University, Mymensingh, Bangladesh during 2005 to 2009. A total of 732 monthly test-day (TD) data of 89 different lactations from 40 selected cows were considered for calculation. The factors for standardizing incomplete lactations to 305-day were constructed by taking 5 calving age groups (< 4, 4-5, 5-6, 6-7 and 7+ years) and two seasons (summer and winter) into consideration with the ratio factors described by established method of estimation